(x^4 - 1)/(x^3) = 0
multiply both sides by x^3.
x^4 - 1 = 0
x^4 = 1
x = +/- 1
2007-08-13 12:13:10
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Provided x is not 0 (in which case the "equation" is meaningless!), multiply by x^3.
Then x^4 - 1 = 0.
Now factorize: (x^2 - 1)(x^2 + 1) = 0, that is
(x - 1)(x + 1)(x^2 + 1) = 0.
Thus there are 4 roots, x = +/- 1 and +/- i, where i is the square root of -1. QED
Live long and prosper.
2007-08-13 12:17:42
·
answer #2
·
answered by Dr Spock 6
·
0⤊
0⤋
15
2007-08-13 12:12:35
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
(x^4 -1) / (x^3)=0
x^4-1 =0 <-- multiply both sides by x^3
x^4 = 1
x = 1,i,-1,-i
2007-08-13 12:21:52
·
answer #4
·
answered by ironduke8159 7
·
0⤊
0⤋
(x^4 -1) / (x^3) = 0
Multiplying both sides by x^3
x^4 - 1 = 0
Factorizing
(x - 1)(x +1)(x^2 + 1) = 0
So
x = 1
x = - 1
x = +- i where i = imaginary number = sqrt of (-1)
2007-08-13 12:19:30
·
answer #5
·
answered by Sheen 4
·
0⤊
0⤋